PTU-233 Transanal haemorrhoidal dearterialization (THD) and targeted mucopexy for haemorrhoids: 215 consecutive patients in a district general hospital. (22nd June 2015) - Joshi, HM; Ormsby, N; Singh, S; Chadwick, M; Scott, M; Samad, A; Rajaganeshan, R
Abstract : Introduction: This study aims to evaluate the efficacy of transanal haemorrhoidal dearterialization and Mucopexy (THD+Mpx) in the treatment of symptomatic haemorrhoids and to identify the factors predicting failure for an effective mid-term outcome. Method: Two hundred and fifteen patients affected by Grade II (27, 13%), III (145, 69%) and IV (39, 18%) symptomatic haemorrhoidal disease underwent THD, with a rectal mucopexy in patients with haemorrhoidal prolapse. The disease was assessed through a specifically designed symptom questionnaire and telephone follow up. A uni- and multivariate analyses of the potential predictive factors for failure were performed. Results: The overall success rate was 91.5% (197 patients) after a mean follow-up period of 10.7 ± 8.7 months, with a recurrence of haemorrhoidal prolapse, bleeding, and both symptoms in 10 (4.7%), 3 (1.4%) and 5 (2.4%) patients, respectively. The morbidity rate was 16.5%, represented mainly by pain or tenesmus (19 patients, 9.0%). Acute bleeding requiring surgical haemostasis occurred in two patients (0.9%). No serious or life-threatening complications occurred. At univariate analysis age less than 45 and absence of any morbidity at 30 days were all variables significantly protecting from failure, the grade of haemorrhoid and recurrent disease were not significantly associated with failure. Conclusion: THD Doppler is a safe and effective therapy for haemorrhoidal disease. A tailored mucopexy is important to contain and reduce the symptoms. Disclosure of interest: None Declared.